A novel herpes simplex virus glycoprotein, gL, forms a complex with glycoprotein H (gH) and affects normal folding and surface expression of gH. - Hutchinson, L (1992)
A glycoprotein encoded by the UL1 gene of herpes simplex virus type 1 (HSV-1) was detected in infected cells with antipeptide sera. The UL1 gene has previously been implicated in virus-induced cell fusion (S. Little and P. A. Schaffer, Virology 112:686-697, 1981). Two protein species, a 30-kDa precursor form and a 40-kDa mature form of the glycoprotein, both of which were modified with N-linked oligosaccharides, were observed. This novel glycoprotein is the 10th HSV-1 glycoprotein to be described and was named glycoprotein L (gL). A complex was formed between gL and gH, a glycoprotein known to be essential for entry of HSV-1 into cells and for virus-induced cell fusion. Previously, it had been reported that gH expressed in the absence of other viral proteins was antigenically abnormal, not processed, and not expressed at the cell surface (U.A. Gompels and A. C. Minson, J. Gen. Virol. 63:4744-4755, 1989; A. J. Forrester, V. Sullivan, A. Simmons, B. A. Blacklaws, G. L. Smith, A. A. Nash, and A. C. Minson, J. Gen. Virol. 72:369-375, 1991). However, gH coexpressed with gL by using vaccinia virus recombinants was antigenically normal, processed normally, and transported to the cell surface. Similarly, gL was dependent on gH for proper posttranslational processing and cell surface expression. These results suggest that it is a hetero-oligomer of gH and gL which is incorporated into virions and transported to the cell surface and which acts during entry of virus into cells.